Professional readiness of physical culture teachers to work with students with health disorders: prospects of development - Dubrov A.A. , (Theory and Practice of Physical Culture, 2025)
The purpose of the study is to identify aspects of the professional readiness of physical education teachers to work with students with disabilities in the context of problems and prospects. Methodology and organization of research. Based on the analysis and generalization of special literature, the concept of "Professional readiness of a physical education teacher to work with students with disabilities" is clarified, the main components of readiness are identified, the features and prospects of additional education of specialists are considered. The results of the study and their discussion. The analysis of the literature made it possible to clarify the concept of "Professional readiness of a physical education teacher to work with students with disabilities", to identify the necessary aspects (components) of readiness, to determine their essence and structure. Prospects for additional education of FC specialists: the use of synergetic and andragogical approaches in advanced training courses (the content of the additional professional program, pedagogical conditions, criteria and diagnostic apparatus). Conclusions. The development of advanced training courses from the perspective of an andragogical approach will contribute to the conscious formation of teachers' professional readiness, taking into account their personal characteristics, professional experience, and motivational guidelines.